Training About Submitting Scientific Articles through OJS (Online Journal System) - Zulkifli Musannip Efendi Siregar Siregar (International Journal Of Community Service, 2021)
The partner in this training was the Faculty of Economics and Business, Universitas Labuhanbatu. The partner's problem was that there were many students who have difficulties regarding the procedure for submitting scientific articles. Therefore, this problem made students difficulty in publishing their scientific work. This training was conducted to transfer knowledge regarding how to submit scientific articles, and also aims to improve students' ability to submit scientific articles. The method used was the lecture method and practice. Approximately 18 students participated in the training. After the workshop or training program, the participants' knowledge and skill to submit the article were more improved.